Main Layers of Phraseological Folklore Systems (Texas Journal of Multidisciplinary Studies, 2022)
The analysis of the denotative-connotative content of the FE of the language of fairy tales, as shown by some of the results accumulated in linguistics, makes it possible to reveal the very essential properties of the phraseological system of folklore. In particular, it is thereby possible to identify specific layers of FE for folklore phraseology. For example, these are "tautological FE" (1) /stable paired words/, which are a notable indicator of Russian folklore phraseology.